Water-based epoxy mortar composite floor coating and preparation method thereof
Patent Information
- Application Number
- CN202610781114.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-02
AI Technical Summary
但是,上述粉体粒径细、比表面积大、表面羟基丰富,直接加入水性环氧砂浆体系时容易团聚,且与水性环氧树脂相的相容性不足,难以充分发挥增强作用
[0050] 1. This invention provides a water-based epoxy mortar composite floor coating and its preparation method. By introducing water-based epoxy emulsion, water-based epoxy curing agent, cement-based mineral aggregate system, and modified composite active filler into components A, B, and C respectively, the resulting coating combines the adhesion, film-forming properties, and water resistance of organic epoxy materials with the high strength, wear resistance, and dimensional stability of cement mortar materials. Compared with ordinary water-based epoxy mortar coatings, this invention, through the compounding of white cement, quartz sand, modified composite active filler, redispersible latex powder, and wear-resistant reinforcing filler, forms a continuous and dense inorganic skeleton and organic-inorganic composite interface within the coating, thereby improving the coating's compressive strength, flexural strength, tensile bond strength, and water resistance retention rate. It is suitable for composite flooring systems with high requirements for load-bearing capacity, wear resistance, and adhesion performance.
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to a water-based epoxy mortar composite floor coating and its preparation method. Background Technology
[0002] Floor coatings are widely used in industrial plants, warehousing and logistics facilities, underground parking garages, laboratories, and other settings. Traditional solvent-based epoxy flooring materials suffer from high volatile organic compound (VOC) release, strong odor during application, and insufficient environmental friendliness. Therefore, water-based epoxy floor coatings, using water as the dispersion medium, are gaining increasing attention. While water-based epoxy floor coatings offer advantages such as low odor, low VOC, and good application safety, they can still experience issues like insufficient coating strength, limited abrasion resistance, and decreased bond strength after water exposure when used in thick coatings, high-load-bearing environments, or on damp substrates.
[0003] To improve the mechanical properties of waterborne epoxy flooring materials, existing technologies typically combine waterborne epoxy resin with white cement, quartz sand, silica fume, and mineral powders to create waterborne epoxy mortar composite flooring coatings. These materials combine the adhesive advantages of epoxy resin with the strength advantages of cement mortar. However, they are multiphase systems containing organic resin, cement hydration, and inorganic aggregate phases. The dispersion state and interfacial bonding between these phases directly affect the coating performance. If the inorganic powder is unevenly dispersed or insufficiently bonded with the resin phase or cement hydration, weak interfacial areas can easily form, leading to problems such as high porosity, uneven local strength, decreased bond strength, whitening after water filtration, powdering, or cracking.
[0004] Active powders such as silica fume, metakaolin, and nano-silica can fill micropores and participate in the later stages of cement hydration, which is beneficial to improving the density and strength of the mortar matrix. However, these powders have fine particle size, large specific surface area, and abundant surface hydroxyl groups, making them prone to agglomeration when directly added to waterborne epoxy mortar systems. Furthermore, their compatibility with the waterborne epoxy resin phase is insufficient, making it difficult to fully exert their reinforcing effect. While single silane modification can improve interfacial bonding, it has limited effect on improving the dispersion stability of the aqueous phase. Although single dispersants or phosphate ester wetting agents can improve wetting and dispersion, their interfacial bridging effect is insufficient. Therefore, it is still necessary to provide a waterborne epoxy mortar composite floor coating and its preparation method that can simultaneously improve the dispersibility, interfacial bonding, mechanical strength, water-resistant adhesion stability, and wear and crack resistance of the composite active filler. Summary of the Invention
[0005] To address the shortcomings of the existing technology, this invention provides a water-based epoxy mortar composite floor coating and its preparation method.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0007] A water-based epoxy mortar composite floor coating, comprising component A, component B and component C;
[0008] Component A comprises an aqueous epoxy emulsion, a wetting and dispersing agent, an aqueous defoamer, an anti-settling thixotropic agent, and water;
[0009] Component B comprises an aqueous epoxy curing agent, water, a film-forming aid, and an interface modifier.
[0010] The C component comprises white cement, quartz sand, modified composite active filler, polycarboxylate superplasticizer, expanding agent, hydroxypropyl methylcellulose ether, redispersible latex powder, and wear-resistant reinforcing filler.
[0011] The modified composite active filler is a composite active powder material obtained by sequentially subjecting a composite powder containing silica fume, metakaolin, and nano-silica to a dual surface modification treatment with a silane coupling agent and a phosphate ester.
[0012] Waterborne epoxy mortar composite floor coatings are multiphase systems containing organic epoxy phases, cement hydration phases, and mineral aggregate phases. While directly adding composite fillers such as silica fume, metakaolin, and nano-silica can provide some filling and activity enhancement, these powders have large specific surface areas and abundant surface hydroxyl groups, making them prone to agglomeration in the aqueous phase. Nano-silica and silica fume, in particular, easily form secondary aggregates, making it difficult to disperse uniformly in the epoxy-cement composite system. Simultaneously, the unmodified inorganic powders lack interfacial compatibility with the waterborne epoxy resin, easily forming weak interfacial zones between the resin and inorganic phases. This leads to problems such as high porosity, uneven local strength, decreased bond strength, and reduced strength retention after water resistance in the later stages of coating development. Based on these shortcomings, this invention synergistically modifies the composite filler with silane and compound phosphate esters, enabling its surface to simultaneously possess inorganic bonding ability, aqueous phase dispersion stability, and epoxy phase compatibility, thereby more effectively exerting its filling, reinforcing, and interfacial bridging functions.
[0013] Preferably, in the raw materials of the modified composite active filler, the weight ratio of silica fume, metakaolin and nano silica is (45-75):(20-40):(4-16).
[0014] Preferably, the quartz sand comprises a mixture of 40-120 mesh quartz sand and 120-300 mesh quartz sand;
[0015] Preferably, the wear-resistant reinforcing filler comprises a mixture of alumina micro powder and wollastonite powder;
[0016] Preferably, the interface modifier is at least one of the following: a pre-hydrolyzed solution of γ-glycidoxypropyltrimethoxysilane and an aqueous polyurethane phosphate dispersion.
[0017] Furthermore, the pre-hydrolyzed solution of γ-glycidoxypropyltrimethoxysilane is prepared by the following method: γ-glycidoxypropyltrimethoxysilane is added to a 40-70 wt% aqueous ethanol solution, wherein the mass ratio of γ-glycidoxypropyltrimethoxysilane to the aqueous ethanol solution is 1:(5-15), the pH is adjusted to 4-5 with glacial acetic acid, and the solution is stirred at 20-30℃ for 20-50 min to obtain the solution.
[0018] Preferably, in component A, the weight ratio of aqueous epoxy emulsion, wetting and dispersing agent, aqueous defoamer, anti-settling thixotropic agent and water is 100:(0.8-1.8):(0.8-2):(0.4-1.2):(8-18).
[0019] Preferably, in component B, the weight ratio of waterborne epoxy curing agent, water, film-forming aid and interface modifier is (40-70):(8-24):(2-7):(1-3).
[0020] Preferably, in component C, the weight ratio of white cement, quartz sand, modified composite active filler, polycarboxylate superplasticizer, expanding agent, hydroxypropyl methylcellulose ether, redispersible latex powder and wear-resistant reinforcing filler is (150-200): (400-500): (40-60): (1-5): (4-10): (0.4-1.2): (8-18): (30-40).
[0021] Preferably, the anti-settling thixotropic agent is fumed silica;
[0022] Preferably, the film-forming aid is selected from at least one of dipropylene glycol butyl ether, dipropylene glycol methyl ether, propylene glycol phenyl ether, tripropylene glycol n-butyl ether, diethylene glycol butyl ether, dodecyl alcohol ester or ethylene glycol monobutyl ether;
[0023] Preferably, the expanding agent is selected from at least one of calcium sulfoaluminate expanding agents, calcium oxide expanding agents, or magnesium expanding agents;
[0024] Preferably, the redispersible latex powder is an ethylene-vinyl acetate copolymer latex powder.
[0025] In this invention, silica fume, metakaolin, and nano-silica are compounded to form multi-scale inorganic active powder. Silica fume and nano-silica can fill the micropores between cement hydration products and quartz sand, and provide nucleation sites for cement hydration products; metakaolin can undergo a pozzolanic reaction with calcium hydroxide in the alkaline environment of cement to generate hydrated calcium silicate and hydrated aluminate products, thereby improving the density and later strength of the mortar matrix.
[0026] After pre-hydrolyzing the silane modifier in an aqueous ethanol solution, its silane groups are converted into silanol groups, which then undergo condensation reactions with the hydroxyl groups on the surfaces of silica fume, metakaolin, and nano-silica, forming a silicon-oxygen bond bonding layer on the surface of the composite powder. Among these, bis-[3-(triethoxysilyl)propyl]amine provides a double-terminated silane anchoring structure and forms compatibility or curing synergy with the aqueous epoxy resin phase through the amine groups; the urea groups in γ-ureopropyltriethoxysilane can form hydrogen bonds with cement hydration products and the surface of aluminosilicates, thereby enhancing the interfacial bonding between the inorganic powder, the epoxy resin phase, and the cement hydration phase.
[0027] The compounded ether-based phosphate wetting agent is further adsorbed onto the surface of the modified powder. The phosphate groups can adsorb or complex with calcium ions and active sites on mineral surfaces in the cement system. The polyether segments improve the wetting and dispersibility of the powder in the aqueous phase, and the aromatic structure enhances its compatibility with waterborne epoxy resin. Therefore, the modified composite active filler can simultaneously perform micropore filling, pozzolanic reaction, silane bridging, and phosphate adsorption, thereby improving the density, bonding strength, shrinkage cracking resistance, and water and abrasion resistance of the waterborne epoxy mortar composite floor coating.
[0028] Preferably, the modified composite active filler is prepared by a method comprising the following steps:
[0029] S1. Mix silica fume, metakaolin, and nano-silica to obtain composite powder;
[0030] S2. The silane coupling agent is pre-hydrolyzed in an acidic alcoholic aqueous solution to obtain a pre-hydrolyzed coupling agent solution;
[0031] S3. The composite powder is added to the pre-hydrolyzed coupling agent solution, and the mixture is stirred and reacted under heating conditions. Then, ether phosphate esters are added to continue the reaction to obtain a modified slurry.
[0032] S4. The modified slurry is filtered, dried, pulverized, and sieved to obtain the modified composite active filler.
[0033] Furthermore, the modified composite active filler is prepared according to the following steps:
[0034] S1. Weigh 45-75 parts by weight of silica fume, 20-40 parts by weight of metakaolin, and 4-16 parts by weight of nano silica, add them to a high-speed mixer, and mix at 600-1000 rpm for 8-15 minutes to obtain composite powder.
[0035] S2. Weigh 2-5 parts by weight of silane coupling agent and add them to 40-100 parts by weight of 40-70 wt% ethanol aqueous solution. Adjust the pH to 4-5 with glacial acetic acid and stir at 200-500 rpm for 20-50 min at 20-30℃ to obtain a pre-hydrolyzed coupling agent solution.
[0036] S3. Add the composite powder obtained in step S1 to the pre-hydrolyzed coupling agent solution obtained in step S2, and stir at 400-700 rpm for 40-90 min at 50-70℃; then add 2-6 parts by weight of ether phosphate ester, and continue stirring at 400-700 rpm for 20-50 min at 50-70℃ to obtain the modified slurry.
[0037] S4. Filter the modified slurry obtained in step S3, dry it with a forced air, crush it and pass it through a 100-300 mesh sieve to obtain the modified composite active filler.
[0038] Preferably, the silane coupling agent is selected from one or more of bis[3-(triethoxysilyl)propyl]amine and γ-ureopropyltriethoxysilane;
[0039] The ether phosphate ester is selected from one or more of fatty alcohol polyoxyethylene ether phosphate ester and aryl polyether phosphate ester; further, the ether phosphate ester is obtained by mixing fatty alcohol polyoxyethylene ether phosphate ester and aryl polyether phosphate ester in a mass ratio of (1-3):1.
[0040] This invention employs a compound phosphate wetting system composed of fatty alcohol polyoxyethylene ether phosphate and styrene-phenol polyoxyethylene ether phosphate. Fatty alcohol polyoxyethylene ether phosphate can improve the wetting and dispersibility of the composite powder in an aqueous phase. The aromatic structure in styrene-phenol polyoxyethylene ether phosphate has good compatibility with waterborne epoxy resin, while the phosphate groups can adsorb calcium ions and mineral powder surfaces in the cement system. Therefore, this compound phosphate wetting system can reduce powder agglomeration, improve mortar flowability, and further enhance the interfacial bonding between the epoxy resin phase, mineral filler phase, and cement hydration phase.
[0041] A method for preparing the water-based epoxy mortar composite floor coating includes the following steps:
[0042] (1) Mix the waterborne epoxy emulsion, wetting and dispersing agent, waterborne defoamer, anti-settling thixotropic agent and water evenly to obtain component A;
[0043] (2) Mix the waterborne epoxy curing agent, water, film-forming aid and interface modifier evenly to obtain component B;
[0044] (3) Mix white cement, quartz sand, modified composite active filler, polycarboxylate superplasticizer, expansion agent, hydroxypropyl methylcellulose ether, redispersible latex powder and wear-resistant reinforcing filler evenly to obtain component C;
[0045] (4) Before construction, mix components A, B and C in proportion to obtain the water-based epoxy mortar composite floor coating.
[0046] Preferably, the mixing mass ratio of component A, component B and component C is (100-130):(65-90):(650-730).
[0047] The stirring speed in step (1) and / or step (2) is 300-500 rpm, and the stirring time is 8-25 min;
[0048] In step (4), after adding component C, the stirring speed is 400-700 rpm and the stirring time is 2-10 min.
[0049] The beneficial effects of this invention are:
[0050] 1. This invention provides a water-based epoxy mortar composite floor coating and its preparation method. By introducing water-based epoxy emulsion, water-based epoxy curing agent, cement-based mineral aggregate system, and modified composite active filler into components A, B, and C respectively, the resulting coating combines the adhesion, film-forming properties, and water resistance of organic epoxy materials with the high strength, wear resistance, and dimensional stability of cement mortar materials. Compared with ordinary water-based epoxy mortar coatings, this invention, through the compounding of white cement, quartz sand, modified composite active filler, redispersible latex powder, and wear-resistant reinforcing filler, forms a continuous and dense inorganic skeleton and organic-inorganic composite interface within the coating, thereby improving the coating's compressive strength, flexural strength, tensile bond strength, and water resistance retention rate. It is suitable for composite flooring systems with high requirements for load-bearing capacity, wear resistance, and adhesion performance.
[0051] 2. This invention uses a composite powder composed of silica fume, metakaolin, and nano-silica as an active filler, and further modifies its surface through a dual process of silane coupling agent and ether phosphate ester. Silica fume and nano-silica can fill the micropores between cement hydration products, quartz sand, and the resin phase, and provide hydration nucleation sites. Metakaolin can react with calcium hydroxide in an alkaline cement system to produce hydrated calcium silicate and hydrated aluminate products, improving the density and later strength of the mortar matrix. Simultaneously, the silane coupling agent can form a silicon-oxygen bond bonding layer on the surface of the composite powder, enhancing the interfacial bonding between the inorganic filler and the aqueous epoxy resin phase and the cement hydration phase. The ether phosphate ester can improve the wetting and dispersibility of the composite powder in the aqueous phase and adsorb calcium ions or mineral surface active sites in the cement system through phosphate groups. Therefore, this invention can effectively reduce composite powder agglomeration, reduce interfacial weak areas, and improve the coating's density, bonding strength, water resistance, and resistance to shrinkage cracking.
[0052] 3. This invention further introduces abrasion-resistant reinforcing fillers composed of alumina micropowder and wollastonite powder, as well as redispersible latex powder of ethylene-vinyl acetate copolymer, into component C. The abrasion-resistant reinforcing fillers can form a hard, abrasion-resistant skeleton in the coating, improving the abrasion resistance and load-bearing stability of the coating surface; the redispersible latex powder can form a flexible polymer film between the cement matrix and the waterborne epoxy resin phase, improving the film continuity, interfacial toughness, and crack resistance of the coating. The coating obtained by this invention exhibits higher 28-day flexural strength, 28-day compressive strength, initial tensile bond strength, and bond strength retention rate after water resistance. After water resistance, there is no blistering, cracking, or peeling, indicating that the components of this invention have a good synergistic reinforcing effect, enabling the production of a waterborne epoxy mortar composite floor coating with high strength, high adhesion, water resistance, abrasion resistance, and crack resistance. Detailed Implementation
[0053] The invention will now be described in further detail with reference to specific embodiments, but it should not be construed as limiting the scope of the invention to the following embodiments.
[0054] The raw materials described in this application are partially described; all other raw materials not described are commercially available.
[0055] The waterborne epoxy emulsion was purchased from Hebei Runbang Chemical Co., Ltd., model: RB-251.
[0056] The white cement was purchased from Shuangshi Mineral Products Processing Plant in Lingshou County. The model number is P.W42.5.
[0057] The silica fume was purchased from Tuolin Mineral Products Processing Plant in Lingshou County, 1250 mesh.
[0058] The water-based epoxy curing agent was purchased from Hebei Runbang Chemical Co., Ltd., model: RB-260.
[0059] The polyether-modified silicone defoamer was purchased from Shanghai Zhenlishi Network Technology Co., Ltd., product number: Tego Foamex1488.
[0060] The ammonium polyacrylate dispersant was purchased from Nanjing Baiju Technology Co., Ltd., model: 5040 dispersant.
[0061] The hydrophilic fumed silica was purchased from Shanghai Wai Dian International Trade Co., Ltd., specification: HDK V15.
[0062] The polycarboxylate superplasticizer was purchased from Shanghai Hengchuang Chemical Co., Ltd., model: PC-1055.
[0063] The ethylene-vinyl acetate copolymer latex powder was purchased from Xiamen Kangdilong Trading Co., Ltd., model: DM200.
[0064] Lauryl alcohol polyoxyethylene ether phosphate was purchased from Nantong Arches Chemical Co., Ltd., model: MOA-3P.
[0065] Nonylphenol polyoxyethylene ether phosphate was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., model number: PB95132.
[0066] Example 1
[0067] A water-based epoxy mortar composite floor coating comprises component A, component B, and component C; component A is composed of the following raw materials in parts by weight: 100 parts by weight of water-based epoxy emulsion, 1.2 parts by weight of wetting and dispersing agent, 1 part by weight of water-based defoamer, 0.8 parts by weight of anti-settling thixotropic agent, and 12 parts by weight of water.
[0068] The wetting and dispersing agent is an ammonium polyacrylate dispersant.
[0069] The water-based defoamer is a polyether-modified silicone defoamer.
[0070] The anti-settling thixotropic agent is hydrophilic fumed silica.
[0071] The B component is composed of the following raw materials in parts by weight: 60 parts by weight of waterborne epoxy curing agent, 15 parts by weight of water, 3 parts by weight of film-forming aid, and 2 parts by weight of interface modifier.
[0072] The film-forming aid is dipropylene glycol butyl ether; the interface modifier is a pre-hydrolyzed solution of γ-glycidoxypropyltrimethoxysilane; the pre-hydrolyzed solution of γ-glycidoxypropyltrimethoxysilane is prepared by the following method: 1 part by weight of γ-glycidoxypropyltrimethoxysilane is added to 9 parts by weight of 50 wt% ethanol aqueous solution, the pH is adjusted to 4.5 with glacial acetic acid, and the solution is stirred at 300 rpm for 30 min at 25 °C to obtain the solution.
[0073] The C component is composed of the following raw materials in parts by weight: 170 parts by weight of white cement, 420 parts by weight of quartz sand, 50 parts by weight of modified composite active filler, 3 parts by weight of PC-1055 polycarboxylate superplasticizer, 6 parts by weight of expansion agent, 0.8 parts by weight of hydroxypropyl methylcellulose ether, 12 parts by weight of redispersible latex powder, and 35 parts by weight of wear-resistant reinforcing filler.
[0074] The expanding agent is calcium sulfoaluminate; the redispersible latex powder is ethylene-vinyl acetate copolymer latex powder.
[0075] The wear-resistant reinforcing filler is obtained by mixing alumina micro powder and wollastonite powder in a mass ratio of 1:1.
[0076] The quartz sand is obtained by mixing 40-120 mesh quartz sand and 120-300 mesh quartz sand in a mass ratio of 1.8:1.0.
[0077] The modified composite active filler is prepared according to the following steps:
[0078] S1. Weigh 60 parts by weight of silica fume, 32 parts by weight of metakaolin, and 8 parts by weight of nano silica, add them to a high-speed mixer, and mix at 800 rpm for 10 min to obtain composite powder.
[0079] S2. Weigh 3.0 parts by weight of silane coupling agent and add it to 60 parts by weight of 60 wt% ethanol aqueous solution. Adjust the pH to 4.5 with glacial acetic acid and stir at 300 rpm for 30 min at 25°C to obtain a pre-hydrolyzed coupling agent solution.
[0080] S3. Add the composite powder obtained in step S1 to the pre-hydrolyzed coupling agent solution obtained in step S2, and stir at 500 rpm for 60 min at 60°C; then add 4 parts by weight of ether phosphate ester, and continue stirring at 500 rpm for 30 min at 60°C to obtain the modified slurry.
[0081] S4. Filter the modified slurry obtained in step S3, dry it with a forced air, crush it and pass it through a 200-mesh sieve to obtain the modified composite active filler.
[0082] The silane coupling agent is bis[3-(triethoxysilane)propyl]amine.
[0083] The ether phosphate ester is obtained by mixing fatty alcohol polyoxyethylene ether phosphate ester and aryl polyether phosphate ester in a mass ratio of 2:1.
[0084] The preparation method of the water-based epoxy mortar composite floor coating includes the following steps:
[0085] (1) Preparation of component A: 100 parts by weight of waterborne epoxy emulsion were added to a dispersion vessel, and stirring was started at a speed of 400 rpm. 1.2 parts by weight of wetting and dispersing agent, 1 part by weight of waterborne defoamer, 0.8 parts by weight of anti-settling thixotropic agent and 12 parts by weight of water were added in sequence, and stirring was continued for 15 min to obtain a uniform component A.
[0086] (2) Preparation of component B: Add 60 parts by weight of waterborne epoxy curing agent to another dispersion vessel, turn on the stirrer and control the speed at 400 rpm; add 15 parts by weight of water, 3 parts by weight of film-forming aid and 2 parts by weight of interface modifier in sequence, and continue stirring for 15 min to obtain a uniform component B.
[0087] (3) Preparation of component C: 170 parts by weight of white cement, 420 parts by weight of quartz sand, 50 parts by weight of modified composite active filler, 3 parts by weight of polycarboxylate superplasticizer, 6 parts by weight of expansion agent, 0.8 parts by weight of hydroxypropyl methylcellulose ether, 12 parts by weight of redispersible latex powder and 35 parts by weight of wear-resistant reinforcing filler were added to a dry powder mixer and mixed at 100 rpm for 10 min to obtain a uniform component C;
[0088] (4) Pre-construction mixing: Weigh each component according to the mass ratio of component A: component B: component C = 115: 80: 696.8; first add component B to component A and stir at 500 rpm for 2 min to obtain epoxy liquid mixture; then add component C to epoxy liquid mixture and stir at 600 rpm for 4 min, let stand for 2 min and stir again for 2 min to obtain water-based epoxy mortar composite floor coating.
[0089] Example 2
[0090] It is basically the same as Example 1, except that the silane coupling agent in the modified composite active filler preparation method is γ-ureidopropyltriethoxysilane.
[0091] Example 3
[0092] It is basically the same as Example 1, except that the ether phosphate ester in the modified composite active filler preparation method is lauryl alcohol polyoxyethylene ether phosphate ester.
[0093] Example 4
[0094] It is basically the same as Example 1, except that the ether phosphate ester in the modified composite active filler preparation method is nonylphenol polyoxyethylene ether phosphate ester.
[0095] Comparative Example 1
[0096] The process is basically the same as in Example 1, except that 50 parts by weight of the modified composite active filler of component C in Example 1 are replaced with 50 parts by weight of the unmodified composite filler. In addition, 60 parts by weight of silica fume, 32 parts by weight of metakaolin, and 8 parts by weight of nano silica are added to a high-speed mixer and mixed at 800 rpm for 10 minutes to obtain the composite filler.
[0097] Comparative Example 2
[0098] The process is basically the same as in Example 1, except that only silane is used for modification and no ether phosphate ester is used. The modified composite active filler is prepared according to the following steps: S1, Weigh 60 parts by weight of silica fume, 32 parts by weight of metakaolin, and 8 parts by weight of nano silica, add them to a high-speed mixer, and mix at 800 rpm for 10 min to obtain composite powder.
[0099] S2. Weigh 3.0 parts by weight of silane coupling agent and add it to 60 parts by weight of 60 wt% ethanol aqueous solution. Adjust the pH to 4.5 with glacial acetic acid and stir at 300 rpm for 30 min at 25°C to obtain a pre-hydrolyzed coupling agent solution. The silane coupling agent is bis[3-(triethoxysilyl)propyl]amine.
[0100] S3. Add the composite powder obtained in step S1 to the pre-hydrolyzed coupling agent solution obtained in step S2, and stir at 500 rpm for 60 min at 60°C to obtain the modified slurry.
[0101] S4. Filter the modified slurry obtained in step S3, dry it with a forced air, crush it and pass it through a 200-mesh sieve to obtain the modified composite active filler.
[0102] Comparative Example 3
[0103] The process is basically the same as in Example 1, except that only ether-based phosphate esters are used, without the use of silanes for modification; the modified composite active filler is prepared according to the following steps:
[0104] S1. Weigh 60 parts by weight of silica fume, 32 parts by weight of metakaolin, and 8 parts by weight of nano silica, add them to a high-speed mixer, and mix at 800 rpm for 10 min to obtain composite powder.
[0105] S2. The composite powder obtained in step S1 is added to 60 parts by weight of an ethanol aqueous solution with a mass fraction of 60 wt%, and stirred at 500 rpm for 60 min at 60 °C; then 4 parts by weight of ether phosphate ester are added, and stirring is continued at 500 rpm for 30 min at 60 °C to obtain a modified slurry; the ether phosphate ester is obtained by mixing fatty alcohol polyoxyethylene ether phosphate ester and aryl polyether phosphate ester in a mass ratio of 2:1;
[0106] S3. Filter the modified slurry obtained in step S2, dry it with a forced air, crush it and pass it through a 200-mesh sieve to obtain the modified composite active filler.
[0107] Comparative Example 4
[0108] The method is basically the same as Example 1, except that the silane coupling agent used in the modified composite active filler preparation method is conventional γ-glycidoxypropyltrimethoxysilane.
[0109] Comparative Example 5
[0110] The method is basically the same as in Example 1, except that: no wear-resistant reinforcing filler is added to component C, and white cement is used instead to reduce the amount; component C is composed of the following raw materials in parts by weight: 205 parts by weight of white cement, 420 parts by weight of quartz sand, 50 parts by weight of modified composite active filler, 3 parts by weight of PC-1055 polycarboxylate superplasticizer, 6 parts by weight of expansion agent, 0.8 parts by weight of hydroxypropyl methylcellulose ether, and 12 parts by weight of redispersible latex powder.
[0111] Comparative Example 6
[0112] The same as in Example 1, except that: no redispersible latex powder was added to component C, and white cement was used instead to reduce the amount;
[0113] The C component is composed of the following raw materials in parts by weight: 182 parts by weight of white cement, 420 parts by weight of quartz sand, 50 parts by weight of modified composite active filler, 3 parts by weight of PC-1055 polycarboxylate superplasticizer, 6 parts by weight of expansion agent, 0.8 parts by weight of hydroxypropyl methylcellulose ether, and 35 parts by weight of wear-resistant reinforcing filler.
[0114] Test Example 1
[0115] Compressive and flexural strength tests: Waterborne epoxy mortar composite floor coatings were prepared according to the methods of Examples 1-4 and Comparative Examples 1-6. The thoroughly mixed samples were placed into triple molds measuring 40mm × 40mm × 160mm, compacted by vibration or slightly leveled, and cured for 24 hours at a temperature of (23±2)℃ and a relative humidity of (50±5)%. The samples were then demolded and cured under the same conditions for 7 days and 28 days, respectively, and the flexural and compressive strengths were tested at 7 days and 28 days.
[0116] Flexural and compressive strength were tested according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". During testing, a three-point flexural test was first performed on a 40mm×40mm×160mm specimen, the failure load was recorded, and the flexural strength was calculated. The two halves of the specimen after flexural testing were then used for compressive strength testing. At least three specimens were tested in each group, and the average value of the results was taken, as shown in Table 1.
[0117] Table 1. Test results of compressive strength and flexural strength
[0118] Example 1 13.9 16.8 47.6 58.4 Example 2 13.2 16.1 46.2 56.9 Example 3 12.7 15.4 44.1 54.6 Example 4 12.9 15.7 44.8 55.2 Comparative Example 1 9.1 11.6 34.6 42.8 Comparative Example 2 11.8 14.3 41.7 51.0 Comparative Example 3 10.6 13.0 38.5 47.2 Comparative Example 4 11.5 14.1 40.8 50.3 Comparative Example 5 11.8 14.6 42.9 52.1 Comparative Example 6 10.9 13.2 39.2 48.5
[0119] Test Example 2
[0120] Tensile bond strength and bond retention rate after water resistance tests: Water-based epoxy mortar composite floor coatings were prepared according to the methods of Examples 1-4 and Comparative Examples 1-6. C30 concrete slabs with polished and dust-removed surfaces were selected as substrates. Each group of samples was coated onto the surface of the concrete slab, with the coating thickness controlled at 3 mm. The coatings were cured for 28 days at a temperature of (23±2)℃ and a relative humidity of (50±5)%.
[0121] Tensile bond strength was tested according to GB / T 22374-2018 "Floor Coating Materials". This standard applies to synthetic resin-based and polymer cement composite floor coating materials applied to cement mortar, concrete, and other substrates for decorative and protective purposes. During testing, a 50mm diameter metal pull-out head was attached to the coating surface. After the adhesive cured, the head was cut along its edge to the substrate surface, and the pull-out test was conducted using a pull-out tester under uniform loading. Each test group consisted of at least five testing points, and the average value was taken after removing obvious outliers.
[0122] The method for testing the bond strength after water resistance is as follows: After curing for 28 days, the specimen is immersed in deionized water at (23±2)℃ for 7 days. After removal, the surface water is wiped off with filter paper. After being placed in a standard environment for 2 hours, the tensile bond strength is tested, and the coating is observed for blistering, cracking, powdering, or peeling. The bond strength retention rate after water resistance is calculated using the following formula:
[0123] The retention rate of bond strength after water resistance / % = tensile bond strength after water resistance / initial tensile bond strength × 100%. Each group was tested 3 times and the average value was taken. The results are shown in Table 2.
[0124] Table 2. Test results of tensile bond strength and bond retention rate after water resistance.
[0125] Example 1 3.12 2.79 89.4 No bubbling, no cracking, no peeling Example 2 2.98 2.62 87.9 No bubbling, no cracking, no peeling Example 3 2.86 2.47 86.4 No bubbling, no cracking, no peeling Example 4 2.91 2.54 87.3 No bubbling, no cracking, no peeling Comparative Example 1 2.05 1.52 74.1 Localized whitening with slight powdering at the edges Comparative Example 2 2.57 2.16 84.0 No obvious blistering, localized whitening Comparative Example 3 2.31 1.86 80.5 Localized whitening indicates a significant decrease in bond strength. Comparative Example 4 2.55 2.09 82.0 Localized whitening, with no obvious peeling. Comparative Example 5 2.76 2.45 84.7 No bubbling, no cracking Comparative Example 6 2.21 1.69 76.5 Slight cracking at the edges, with localized whitening.
[0126] As shown in Tables 1 and 2, the waterborne epoxy mortar composite floor coating prepared by this invention exhibits good flexural strength, compressive strength, initial tensile bond strength, and retention rate of bond strength after water resistance. Among them, Example 1 shows the best performance, indicating that the use of bis[3-(triethoxysilyl)propyl]amine as a silane coupling agent, combined with a compound ether phosphate ester composed of fatty alcohol polyoxyethylene ether phosphate and aryl polyether phosphate, for dual surface modification of the composite active filler can simultaneously improve the dispersibility, interfacial bonding ability, and overall density of the waterborne epoxy composite coating, thereby giving the coating high mechanical strength, substrate bonding strength, and water resistance stability.
[0127] In Example 2, simply replacing the silane coupling agent with γ-ureidopropyltriethoxysilane resulted in a certain degree of decrease in 28-day compressive strength, initial tensile bond strength, and strength retention after water resistance. This indicates that although γ-ureidopropyltriethoxysilane can form certain hydrogen bonds with the surface of inorganic minerals or cement hydration products through urea groups, its interfacial bridging and curing synergistic effect on the waterborne epoxy resin phase is weaker than that of bis[3-(triethoxysilyl)propyl]amine. Bis[3-(triethoxysilyl)propyl]amine has a double-ended silane anchoring structure and contains an amine group structure, which is more conducive to forming stable interfacial connections between the inorganic filler surface, cement hydration products, and epoxy resin phase. In Examples 3 and 4, replacing the compounded ether phosphate ester with single fatty alcohol polyoxyethylene ether phosphate ester or single aryl polyether phosphate ester, respectively, resulted in lower overall performance than in Example 1. The reason is that fatty alcohol polyoxyethylene ether phosphates are more inclined to improve the wetting and dispersibility of powders in the aqueous phase, but their compatibility with the aqueous epoxy resin phase is relatively insufficient; aryl polyether phosphates have better compatibility with the epoxy resin phase, but when used alone, their improvement on the wetting and dispersion retention of powders in the aqueous phase is not as sufficient as that of the compound system. In Example 1, the two ether phosphates, when compounded, can take into account the dispersion in the aqueous phase, the adsorption on the mineral surface, and the compatibility with the epoxy phase, so that the composite filler is more evenly distributed in the system, the interfacial bonding is more stable, and ultimately has higher strength and adhesion retention rate.
[0128] Comparative Example 1, using unmodified composite fillers, showed a significant decrease in 28-day flexural strength, 28-day compressive strength, initial tensile bond strength, tensile bond strength after water resistance, and strength retention rate. This indicates that while silica fume, metakaolin, and nano-silica possess filling and potential active reinforcing effects, without surface modification, their large specific surface area and numerous surface hydroxyl groups make them prone to agglomeration in water-based epoxy and cement systems. This leads to increased local porosity and weak interfacial areas, preventing them from fully realizing their filling, densifying, and interfacial reinforcing effects. The localized whitening and slight edge powdering after water resistance further demonstrate insufficient bonding between the unmodified composite fillers and the epoxy resin and cement hydration phases, making it easier for moisture to weaken interfacial adhesion.
[0129] Comparative Example 2 used only silane modification without ether phosphate esters, and Comparative Example 3 used only ether phosphate ester treatment without silane modification. Both showed better performance than Comparative Example 1, but were still significantly lower than Example 1. This indicates that silane modification is more direct in improving the interfacial bonding between inorganic powder and the epoxy resin phase and cement hydration phase; however, with only silane modification, the wetting, dispersion, and flow retention of the powder in the aqueous phase are still insufficient, and the agglomeration problem cannot be fully eliminated. With only ether phosphate esters, although powder wetting and dispersion can be improved, the lack of an interfacial bridging layer formed by silane limits the improvement in strength and water resistance. Comparative Example 4 used conventional γ-glycidyl etheroxypropyltrimethoxysilane instead of the preferred bis[3-(triethoxysilyl)propyl]amine, and the effect was also reduced. This indicates that while conventional epoxy silanes can improve the compatibility between inorganic fillers and the resin phase to some extent, their interfacial anchoring ability, compatibility with the cement hydration phase, and synergistic effect with the curing system are inferior to bis[3-(triethoxysilyl)propyl]amine. Comparative Example 5, without the addition of abrasion-resistant reinforcing filler, and Comparative Example 6, without the addition of redispersible latex powder, both showed varying degrees of performance degradation. This indicates that in addition to primarily improving the abrasion resistance of the coating, the abrasion-resistant reinforcing filler can also form a certain hard micro-skeleton through alumina micropowder and wollastonite powder, improving the filling density and load-bearing capacity of the coating. The weakening of the hard abrasion-resistant skeleton and the auxiliary reinforcing effect of fibrous / acicular minerals in the system resulted in a decrease in compressive strength and bond strength. However, due to the presence of the modified composite active filler, the main interfacial reinforcement mechanism of the system was not completely lost. Furthermore, slight edge cracking and localized whitening occurred after water resistance. These results demonstrate that redispersible latex powder plays an important role in the bonding stability and crack resistance of waterborne epoxy mortar composite floor coatings. It can form a flexible polymer film between the cement matrix and the epoxy resin phase, improving the film continuity, interfacial toughness and stress buffering capacity of the coating. When this component is missing, the internal brittleness of the coating increases, and stress concentration and adhesion attenuation are more likely to occur at the interface after the action of moisture. Therefore, its adhesion retention rate after water resistance is significantly reduced.
Claims
1. A water-based epoxy mortar composite floor coating, characterized in that, It contains components A, B, and C; Component A comprises an aqueous epoxy emulsion, a wetting and dispersing agent, an aqueous defoamer, an anti-settling thixotropic agent, and water; Component B comprises an aqueous epoxy curing agent, water, a film-forming aid, and an interface modifier. The C component comprises white cement, quartz sand, modified composite active filler, polycarboxylate superplasticizer, expanding agent, hydroxypropyl methylcellulose ether, redispersible latex powder, and wear-resistant reinforcing filler. In component A, the weight ratio of aqueous epoxy emulsion, wetting and dispersing agent, aqueous defoamer, anti-settling thixotropic agent and water is 100: (0.8-1.8): (0.8-2): (0.4-1.2): (8-18). In component B, the weight ratio of waterborne epoxy curing agent, water, film-forming aid and interface modifier is (40-70): (8-24): (2-7): (1-3). In component C, the weight ratio of white cement, quartz sand, modified composite active filler, polycarboxylate superplasticizer, expanding agent, hydroxypropyl methylcellulose ether, redispersible latex powder, and wear-resistant reinforcing filler is (150-200): (400-500): (40-60): (1-5): (4-10): (0.4-1.2): (8-18): (30-40). The modified composite active filler is a composite active powder material obtained by sequentially subjecting a composite powder containing silica fume, metakaolin, and nano silica to a dual surface modification treatment with a silane coupling agent and an ether phosphate ester. The silane coupling agent is selected from one or more of bis[3-(triethoxysilyl)propyl]amine and γ-ureopropyltriethoxysilane; The ether phosphate ester is obtained by mixing fatty alcohol polyoxyethylene ether phosphate ester and aryl polyether phosphate ester in a mass ratio of (1-3):
1.
2. The water-based epoxy mortar composite floor coating according to claim 1, characterized in that, In the raw materials of the modified composite active filler, the weight ratio of silica fume, metakaolin and nano silica is (45-75):(20-40):(4-16).
3. The water-based epoxy mortar composite floor coating according to claim 1, characterized in that, The quartz sand comprises a mixture of 40-120 mesh quartz sand and 120-300 mesh quartz sand; The wear-resistant reinforcing filler comprises a mixture of alumina micro powder and wollastonite powder; The interface modifier is at least one of the following: a pre-hydrolyzed solution of γ-glycidoxypropyltrimethoxysilane and an aqueous polyurethane phosphate dispersion.
4. The water-based epoxy mortar composite floor coating according to claim 1, characterized in that, The anti-settling thixotropic agent is fumed silica; The film-forming aid is selected from at least one of dipropylene glycol butyl ether, dipropylene glycol methyl ether, propylene glycol phenyl ether, tripropylene glycol n-butyl ether, diethylene glycol butyl ether, dodecyl alcohol ester or ethylene glycol monobutyl ether; The expanding agent is selected from at least one of calcium sulfoaluminate expanding agents, calcium oxide expanding agents, or magnesium expanding agents; The redispersible latex powder is an ethylene-vinyl acetate copolymer latex powder.
5. The water-based epoxy mortar composite floor coating according to claim 1, characterized in that, The modified composite active filler is prepared by a method comprising the following steps: S1. Mix silica fume, metakaolin, and nano-silica to obtain composite powder; S2. The silane coupling agent is pre-hydrolyzed in an acidic alcoholic aqueous solution to obtain a pre-hydrolyzed coupling agent solution; S3. The composite powder is added to the pre-hydrolyzed coupling agent solution, and the mixture is stirred and reacted under heating conditions. Then, ether phosphate esters are added to continue the reaction to obtain a modified slurry. S4. The modified slurry is filtered, dried, pulverized, and sieved to obtain the modified composite active filler.
6. A method for preparing the water-based epoxy mortar composite floor coating according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Mix the waterborne epoxy emulsion, wetting and dispersing agent, waterborne defoamer, anti-settling thixotropic agent and water evenly to obtain component A; (2) Mix the waterborne epoxy curing agent, water, film-forming aid and interface modifier evenly to obtain component B; (3) Mix white cement, quartz sand, modified composite active filler, polycarboxylate superplasticizer, expansion agent, hydroxypropyl methylcellulose ether, redispersible latex powder and wear-resistant reinforcing filler evenly to obtain component C; (4) Before construction, mix components A, B and C in proportion to obtain the water-based epoxy mortar composite floor coating.
7. The method according to claim 6, characterized in that, The mixing mass ratio of components A, B and C in step (4) is (100-130):(65-90):(650-730). The stirring speed in step (1) and / or step (2) is 300-500 rpm, and the stirring time is 8-25 min; In step (4), component B is first added to component A and stirred at 400-600 rpm for 1-3 minutes to obtain epoxy liquid mixture; then component C is added and the stirring speed is 400-700 rpm for 2-10 minutes to obtain the water-based epoxy mortar composite floor coating.
Citation Information
Patent Citations
Epoxy resin mortar composite used for plate type fragment-free track
CN101560077A
Adhesive force promoting material as well as preparation method and application thereof
CN112852214A